SOCIO-ECONOMIC ASPECTS OF RURAL DEVELOPMENT IN UZBEKISTAN - Saidova Dildora Nurmatovna (Journals Park Publishing, 2023)
The article examines the socio-economic aspects of the development of rural areas. Analyzed the state of rural areas. The reasons for the lag in the development of rural areas are revealed. Recommendations for the sustainable development of rural areas have been developed.
Keywords: rural areas, rural economy , sustainable growth, poverty level, socio-economic development.